Case Report: Heart Transplantation for Refractory Candida tropicalis Endocarditis: A Case Report and Literature Review - Ricardo El Nouwar; Eva Larranaga Lapique; Frédéric Vanden Eynden; Delphine Martiny; Myriam Remmelink; Ana Roussoulières; Maya Hites (Microorganisms)
Candida infective endocarditis presents therapeutic challenges with high mortality. A complex case of Candida prosthetic valve endocarditis refractory to standard antifungals (anidulafungin and fluconazole) and high-dose caspofungin was successfully treated with heart transplantation. The literature review revealed a few cases of bacterial endocarditis successfully treated with heart transplantation, but with only two transplanted cases of fungal endocarditis. This report explores heart transplantation as a last resort for managing refractory infective endocarditis. The patient is still alive and free of infection, two and a half years after transplantation.